A bibliographic survey of the supramolecular architectures sustained by delocalised C–I⋯π(arene) interactions in metal-organic crystals. - Tiekink, Edward R. T. * (De Gruyter, 2022)
A survey of the crystallographic literature of metal-organic crystals for the presence of C– I···π(arene) interactions where the iodide atom occupies a position close to plumb to the ring centroid, corresponding to a delocalised interaction, and is within the assumed sum of the van der Waals radii, i.e. 3.88 Å, has been undertaken. The majority of the 26 identified examples feature supramolecular chains of varying topology whereby C–I···π(arene) contacts are readily identified and apparently operating independently of other obvious supramolecular synthons. The next most prevalent supramolecular aggregate was zero-dimensional, containing up to a maximum of three molecules. While there were three examples of two-dimensional arrays among a series of isostructural crystals, no examples of three-dimensional frameworks largely sustained by C–I···π(arene) interactions were noted. This distribution of supramolecular aggregation patterns matched that noted for all-organic systems. In terms of the overall adoption rate, delocalised C–I···π(arene) interactions were found in 3% of crystals of metalorganic species where they could form, a percentage lower than 4% noted for all-organic crystals.